The tenure track employment system in colleges and universities in China: a scoping review of the Chinese literature - Wang, Xin; Wang, Wen Li (Frontiers in Psychology, 2024)
Chinese higher education institutions have adopted a US-style tenure track system since the 1990s. This is an important reform aimed at modernizing China’s higher education system. In response, authors have begun to carry out close examination of the career system and analyse its implications in a national context (Republic of China). This study aims to present the key research themes, identify research gaps and offer recommendations from the increasing pool of Chinese-language literature on the tenure track system. A scoping review of Chinese language papers was conducted using the China National Knowledge Infrastructure (including the China Academic Journals Full-text Database, China Core Newspapers Full-text Database, China Doctoral Dissertations Full-text Database, China Masters’ Thesis Full-text Database, and China Yearbooks Full-text Database) (CNKI) database. Four major research themes were identified in Chinese discourse: (1) examining the tenure track system, (2) providing suggestions for better adaptation of the tenure track system in the Chinese context, (3) analysing the negative effects of the tenure track system, and (4) analysing the positive effects of the tenure track system. Generally, authors were concerned with the adaptation and cultivation of the US-originated tenure track system in the Chinese context and emphasized the importance of acknowledging its perceived negative influences on early-career scholars who have not received adequate attention. Overall, the authors demonstrate increasing interest in the tenure track system in China, and the literature is of variable quality. Further empirical studies are needed to analyse, evaluate and guide future improvement of the career system in the Chinese context in practice.